1976
DOI: 10.1093/ajcp/66.3.526
|View full text |Cite
|
Sign up to set email alerts
|

Brain-stem and Adrenal Abnormalities in the Sudden-infant-death Syndrome

Abstract: Fourteen of 28 sudden-infant-death syndrome (SIDS) victims had an abnormal proliferation of astroglial fibers in their brain stems and an enlarged mass of chromaffin cells in their adrenal medullas. Both of these abnormalities were associated with greater than normal muscle in the small pulmonary arteries, abnormal brown fat retention, and retained extramedullary erythropoiesis. These latter three findings are probably evidences of chronic alveolar hypoventilation and hypoxemia. The brain stem and adrenal abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
2

Year Published

1979
1979
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(92 citation statements)
references
References 0 publications
3
85
0
2
Order By: Relevance
“…The greater increase in ventilation with Con found in aborted SIDS infants at 3 and 4 months of age is consistent with this hypothesis because it has been shown experimentally that acutely injected epinephrine or norepinephrine in adult man causes a greater increase in ventilation in response to C 0 2 (4, 7, 9). Additional support for this hypothesis is provided by the postmortem observation demonstrating hypertrophy of the chromaffin cell layer of the adrenal medulla in victims of SIDS (25).…”
Section: Resting Ventilation In Aborted Slds Infantsmentioning
confidence: 88%
“…The greater increase in ventilation with Con found in aborted SIDS infants at 3 and 4 months of age is consistent with this hypothesis because it has been shown experimentally that acutely injected epinephrine or norepinephrine in adult man causes a greater increase in ventilation in response to C 0 2 (4, 7, 9). Additional support for this hypothesis is provided by the postmortem observation demonstrating hypertrophy of the chromaffin cell layer of the adrenal medulla in victims of SIDS (25).…”
Section: Resting Ventilation In Aborted Slds Infantsmentioning
confidence: 88%
“…12 He concluded that these changes were caused by hypoxia and were not the cause of SIDS. Kinney and colleagues 15 also found gliosis in 22% of their SIDS victims and instituted studies of neurotransmitter systems in the brainstem, particularly muscarinic and serotenergic systems.…”
Section: Discussionmentioning
confidence: 99%
“…6 Naeye reported in 1976 significant proliferation of astroglial fibers in the brainstem of half of his SIDS cases 12 ; the other half had no more nor less astrogliosis than did controls who had died of trauma or acute asphyxia. (Because 4 days or more are required to develop astrogliosis, 13 its presence cannot be attributed to a single acute episode ending in death.)…”
Section: Vulnerable Infantmentioning
confidence: 99%
“…Understanding the role of medullary 5-HT neurons in sleep and thermoregulation may help us determine mechanisms involved in sudden infant death syndrome (SIDS), where abnormalities in thermoregulation and arousal have been implicated (21,22,38,39,57,83,91). Almost 75% of SIDS infants studied have decreased binding to 5-HT 1A receptors and increased numbers of 5-HT neurons in all of the medullary serotonergic nuclei, including the medullary raphé and PGCL (41-43, 65, 69), groups of neurons homologous to those that have been found to be important in thermoregulation and sleep in animals (12,17,53).…”
Section: Methoxyphenyl)-1-piperazinyl]-mentioning
confidence: 99%